Viewman Engineering Sdn Bhd / Nur Syafiqah Saimi - Saimi, Nur Syafiqah (2017)
Through this Industrial Training, it will help students to understand more about the field of their study. By involving students in this training, it helps to produce skilful employee in the future as they have experienced and was exposed to it. Students were able to discover their own ability through this training as they coworker with people who are more matured than them. This training also able to teach them to be more discipline and responsible for each and every work they are assign to do. Usually, students in semester 4 and above will undergo industrial training during the semester break. As a requirement to graduate, students of Diploma in Civil Engineering must complete Industrial Training for 8 weeks.